2010
DOI: 10.1159/000275674
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effects of Therapeutic Cholinesterase Inhibitors on Visuospatial Processing in Alzheimer’s Disease: A Longitudinal Functional MRI Study

Abstract: Background/Aims: Visuospatial impairments are known to occur in Alzheimer’s disease (AD). We hypothesised that functional magnetic resonance imaging (fMRI) response in task-related brain regions would be impaired in patients with AD during the task and that treatment with acetyl cholinesterase inhibitors would enhance activations in brain regions concerned with this visual perceptual processing. Method: Ten AD subjects were neuropsychologically assessed and underwent fMRI imaging whilst performing a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 120 publications
0
18
0
Order By: Relevance
“…The use of PPI allowed us to globally assess regions functionally associated with M1, addressing the limitation of model-based connectivity analysis 11 . However, unlike Agosta et al 53 we cannot infer direct connectivity between regions. Further, 6 participants with AD were on an established regimen of an acetylcholinesterase inhibitor, a known modifier of cortical activation.…”
Section: Discussionmentioning
confidence: 56%
“…The use of PPI allowed us to globally assess regions functionally associated with M1, addressing the limitation of model-based connectivity analysis 11 . However, unlike Agosta et al 53 we cannot infer direct connectivity between regions. Further, 6 participants with AD were on an established regimen of an acetylcholinesterase inhibitor, a known modifier of cortical activation.…”
Section: Discussionmentioning
confidence: 56%
“…However, previous studies evaluating activation changes in response to treatment with ChEIs have shown drug effects in both the left and right medial temporal lobes during episodic encoding and recognition (16, 19). Studies of fMRI activation during other cognitive tasks, such as a visual attention task and a location-matching task, have also shown activation changed in both left and right medial temporal lobes in response to ChEI treatment in AD and MCI patients (20, 22, 23, 27). Furthermore, improved cognitive performance has been associated with increased activation in both the left and right medial temporal lobes after treatment with donepezil (31).…”
Section: Discussionmentioning
confidence: 99%
“…In AD patients, acute dosing with ChEIs resulted in primarily increased activation post-drug treatment during episodic face encoding and recognition, working memory, and visual and attention tasks in task-related regions (15, 19, 22, 29). Chronic dosing of AD patients with ChEIs for varying periods (10–24 weeks) also showed a post-drug effect on brain activation, with patients showing increased activation during episodic encoding and recognition, semantic association, working memory, and visuospatial perceptual tasks in task-related areas (18, 21, 27, 29). Increased activation in task-related regions during episodic encoding after ChEI treatment in AD patients was also associated with improved clinical memory performance (31).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Woodruff's research group sought to test the rationale for use of cholinesterase inhibitors to reduce visuospatial impairments with AD (Thiyagesh et al 2010). They did this using a small patient population studied with an fMRI visuospatial processing task before and after cholinesterase inhibition.…”
Section: Defining Treatment-relevant Pd Effectsmentioning
confidence: 99%